(untitled) (Bangladesh Journal of Medical Science, 2018)
Objectives: The main aim of this study was to describe the neonatal outcomes of term neonates following initial hospital discharge. Methods: This is a descriptive cross sectional study done among term neonates discharged from Teaching Hospital (TH) Kandy from 27th of March to 14th of May 2015. All the term neonates who delivered at term in the TH Kandy during the study period were included in the study. Study was conducted as a telephone survey. Results: Nearly half (46.79%) of the mothers sought medical advice for their neonates following hospital discharge during the neonatal period. Majority of the mothers who sought medical advice (71.06%) went to ordinary doctors while 28.43% consulted specialist doctors. All most all women (98.10%) exclusively breast fed their newborn baby. Four percent of the term neonates were hospitalized during the neonatal period and most common reasons for admission was breathing difficulty followed by yellow discoloration of the body. Considerable proportion (29.66%) of mothers stated that postnatal visits were not helpful for any of the six aspects of postnatal care questioned in the telephone interview. Postpartum visits had its highest impact on breastfeeding followed by maternal competence on recognizing danger signs. But post-partum visit had its least impact on keeping baby warm and dressing up of baby. Conclusion: Nearly half of the mothers seek medical advice for their neonates following hospital discharge during the neonatal period. One third of the mother stated that postnatal visits were not helpful for any of the six aspects of postnatal care studied. Postpartum visits had its highest impact on breastfeeding followed by maternal competence on recognizing danger signs while had its least impact on keeping baby warm and dressing up of baby. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.194-199